Capital Structure of Thai Firms - Target and Crisis - Tunvirachaisakul, Khaomai (2005)
This dissertation is the result of the research carried out to study the capital structures of 80 non-financial firms across 8 industries in Thailand. The capital structures in this case include the study of 6 ratios which regarding to debt-to-equity, debt-to-assets, and equity-to-assets. Therefore, they can be named as - the study of debt-equity structures.